Construction of minimally-sheltered knockouts mutants of Neurospora crassa - Robert L. Metzenberg (Fungal Genetics Reports, 2005)
I have been developing strains which I think will make it possible to produce "minimally-sheltered knockouts" of essential genes routinely. They could equally well be called "self-adjusting knockdowns" of essential genes. Such minimally-sheltered knockouts could give results in microarray analysis that would be less subject to artifact than results with heterokaryons or with homokaryons sheltered with an inducible wild-type allele of the gene in question. The method addresses two questions about each cloned gene, henceforth and collectively called "your favorite gene" (yfg). yfg should be one which does not pass successfully through a cross as a hygromycin-resistant knockout. (1) Is yfg a dispensable gene? (2) If yfg is found to be essential, what is the "terminal phenotype" of the yfgΔ knockout mutation? By "terminal phenotype," I mean that of the heterokaryon between yfgΔ and a partial diploid, yfg+/Δ, in which the partial diploid is the minimum proportion that allows somewhat suboptimal growth.